Contact Alopecia: Improvement of Alopecia with Discontinuation of Fluocinolone Oil in Individuals Allergic to Balsam Fragrance. Issue 1 (25th October 2016) - Admani, Shehla; Goldenberg, Alina; Jacob, Sharon E.
Abstract: Inflammatory scalp dermatoses can be associated with alopecia, which is nonscarring and reversible in its early stages. This association has been described in seborrheic dermatitis, psoriasis, and atopic dermatitis. We describe three girls with alopecia aggravated by contact allergy to balsam fragrances. All three had complete resolution with avoidance of balsam of Peru and other balsam derivatives (including discontinuation of fluocinolone oil, which contains balsam of pine).